Keroncong Arrangement as an Expression of Freedom Congrock 17 - Satria, Dioda; Setiawan, Aris; Darlenis, Teti (Institut Seni Indonesia Yogyakarta, 2024)
This study aims to analyze the results of the arrangement of keroncong music performed by Congrock 17. Congrock 17 is a well-known progressive keroncong music group from Semarang City, Central Java, Indonesia. This study’s two musical works are the object of analysis: Keroncong Pemuda-Pemudi and Perdamaian. This study uses a musicological approach emphasizing the concepts of arrangement, freedom, expression, and musical form. These concepts determine how far Congrock 17 can create new characters and nuances in existing musical works. Musical considerations were made by Congrock 17 by keeping the fundamental nature of keroncong the same, especially in the use of musical instruments such as cak, cuk, bass, violin, and cello. As a result, the arrangement of old works by Congrong 17 was intended so that keroncong would develop more progressively, be liked by the younger generation, and avoid monotony.